Recent modeling for the ITER ion cyclotron range of frequency antennas with the TOPICA code. (1st April 2023) - Milanesio, D.; Helou, W.; Polli, V.; Durodié, F.; Lamalle, P.; Maquet, V.; Messiaen, A.; Tierens, W.; Zhang, W.
Abstract: This paper documents the analysis of the ITER ion cyclotron resonance heating (ICRF) launcher using the TOPICA code, throughout recent years' design activities. The ability to simulate the detailed geometry of an ICRF antenna in front of a realistic plasma and to obtain the antenna input parameters, the electric currents on conductors and the radiated field distribution next to the antenna is of significant importance to evaluate and predict the overall system performances. Starting from a reference geometry, we first investigated the impact of some geometrical and numerical factors, such as the Faraday Screen geometry or the mesh quality. Then a final geometry was the object of a comprehensive analysis, varying the working frequency, the plasma conditions and the poloidal and toroidal phasings between the feeding lines. The performance of the antenna has been documented in terms of input parameters, power coupled to plasma and electric fields. Eventually, the four-port junction has also been included in TOPICA models.